2022
DOI: 10.3390/f13081273
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Accuracy of Modulus of Elasticity (MOE) in the Wood of Standing Trees and Logs

Abstract: The characterization of poplar wood assumes a strategic position to increase the competitiveness of the entire forest wood supply chain. From this aspect, the identification of wood quality represents a primary objective for researchers and private landowners. The quality of wood can be defined via traditional visual methods based on the experience of technicians or using traditional tools, such as incremental drills and sound hammers. The traditional properties of these traits, based only on visual characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In this study, we found a correlation between the acoustic velocity and static MOE on slabs for all six trees. A study reported by Papandrea et al (2022) also shows a correlation between the velocity and the MOE of logs of the poplar trees. Van & Schimleck (2022) reported that the Eucalyptus clone shows a positive correlation between the acoustic velocity and the MOE.…”
Section: Acoustic Velocity Dynamic Moe and Static Moementioning
confidence: 58%
“…In this study, we found a correlation between the acoustic velocity and static MOE on slabs for all six trees. A study reported by Papandrea et al (2022) also shows a correlation between the velocity and the MOE of logs of the poplar trees. Van & Schimleck (2022) reported that the Eucalyptus clone shows a positive correlation between the acoustic velocity and the MOE.…”
Section: Acoustic Velocity Dynamic Moe and Static Moementioning
confidence: 58%
“…In severely decayed trees, such as those in this study, this variability may be even greater, as damaged wood has been shown to be much tougher than normal wood [30]. Even under ideal conditions, the correlation between stress wave velocity and the modulus of rupture can be quite low [25,[31][32][33]. Wood is an anisotropic material with a different material response depending on the direction of the applied stress.…”
Section: Discussionmentioning
confidence: 79%
“…The influence of climate circumstances on the GRW for Populus ussuriensis Kom (Gou and Chen 2011), Canadian poplar (Populus x canadensis Moench) (Ziemiańska and Kalbarczyk 2018), and Populus hybrids in Latvia (Šēnhofa et al 2016), and length and temperature of the day on the ring properties of Populus alba L. (Baba et al 2022) were evaluated relative to the interaction with mechanical properties. Lang et al (2002Lang et al ( , 2003, Roohnia et al (2010), Casado et al (2010), Ettelaei et al (2019), Virgen-Cobos et al (2022, Papandrea et al (2022), Zhang and Lu (2014), Rescalvo et al (2020), Hajihassani et al (2018), Özkan et al (2020), Narasimhamurthy et al (2017), Aydın et al (2007), Monteior et al (2019, Sözbir et al (2019) dynamically and/or statically determined the EL of different poplar species as solid wood (unmodified or modified), standing trees, or engineered products prepared from Populus x canadensis. A few studies considered the shear modulus or full (twelve) elastic constants.…”
Section: Introductionmentioning
confidence: 99%